المكانة الاجتماعية للمرأة العاملة المتزوجة في الأسرة الجزائرية - تواتي عبدالله; مامنية سامية (University of Eloued جامعة الوادي, 2024)
ملخص: إن خروج المرأة للعمل هو واقع استحدث في العصر الحديث بسبب الاحتياجات التي أجبرت المرأة على ذلك، وهناك من عارض عمل المرأة خوفا من التفكك الأسري الذي سوف يحدث للأسرة، وهناك من وصفه بالعمل النبيل الذي ترتقي به الأمم، ومن خلال هذا المقال سوف نتطرق إلى استبيان العلاقة بين عمل المرأة ومكانتها الاجتماعية داخل الأسرة الجزائرية وذلك من خلال تساؤل رئيسي لهذه الدراسة والمتمثل في، هل تختلف مكانة المرأة العاملة بالاختلاف أدوارها الوظيفية داخل الأسرة؟ وقد تم الاعتماد في هذه الدراسة على العينة القصدية التي تمثلت في المرأة العاملة المتزوجة بكلية العلوم الإنسانية والاجتماعية في جامعة سكيكدة والتي قدرت ب 30 امرأة (مفردة)، كما اعتمدت هذه الدراسة على المنهج الوصفي الذي يمكن الباحث من جمع البيانات والمعلومات التي تصف الظاهرة وصفا كيفي، وقد تم الاعتماد كذلك على أداة جمع المعلومات والمتمثلة في الاستمارة وقد توصلت هذه الدراسة على عدة نتائج كان من أبرزها: وهي أن علاقة عمل المرأة ومكانتها الاجتماعية داخل الأسرة يتحدد من خلال سلطتها داخل الأسرة ومن خلال دورها ونوع عملها الذي تمارسه في المجتمع هما اللذان يحددان مكانتها داخل أسرتها والمجتمع.Abstract: The exit of women to work is a reality developed in the modern era because of the needs that forced women to do so, and there are those who opposed women's work for fear of family disintegration that will happen to the family, and there are those who described it as a noble work that nations elevate, and through this article we will address the questionnaire of the relationship between women's work and their social status within the Algerian family, through a key question for this study, which is, Does the status of working women differ according to their functional roles within the family? This study was based on the intentional sample represented in the married working woman at the Faculty of Humanities and Social Sciences at the University of Skikda, which was estimated at 30 women (single), and this study also relied on the descriptive approach that enables the researcher to collect data and information that describe the phenomenon qualitatively, and has also been relying on the information collection tool represented in the form This study reached several results, the most prominent of which were: It is that a woman's working relationship and social status within the family are determined by her authority within the family and by her role and type of work in society that determine her position within her family and society.
Keywords: المرأة العاملة; المكانة الاجتماعية; الأسرة; SOCIAL SCIENCES::Social sciences::Social work::Family research; Working Women; Social status